Neural Correlates of Moral Evaluation and Psychopathic Traits in Male Multi-Problem Young Adults - Zijlmans, Josjan; Marhe, Reshmi; Bevaart, Floor; Luijks, Marie-Jolette A.; van Duin, Laura; Tiemeier, Henning; Popma, Arne (Frontiers in Psychiatry, 2018)
Multi-problem young adults (18-27 years) present with a plethora of problems, including varying degrees of psychopathic traits. The amygdala and ventromedial prefrontal cortex (vmPFC) have been implicated in moral dysfunction in psychopathy in adolescents and adults, but no studies have been performed in populations in the transitional period to adulthood. We tested in multi-problem young adults the hypothesis that psychopathic traits are related to amygdala and vmPFC activity during moral evaluation. Additionally, we explored the relation between psychopathic traits and other regions consistently implicated in moral evaluation. Our final sample consisted of 100 multi-problem young adults and 22 healthy controls. During fMRI scanning, participants judged whether pictures showed a moral violation on a 1-4 scale. Whole brain analysis revealed neural correlates of moral evaluation consistent with the literature. Region of interest analyses revealed positive associations between the affective callous-unemotional dimension of psychopathy and activation in the left vmPFC, left superior temporal gyrus, and left cingulate. Our results are consistent with altered vmPFC function during moral evaluation in psychopathy, but we did not find evidence for amygdala involvement. Our findings indicate the affective callous-unemotional trait of psychopathy may be related to widespread altered activation patterns during moral evaluation in multi-problem young adults.